Synthesis and investigation of the physical-chemical properties of 2-(5-((theophylline-7’-yl)methyl)-4-methyl-4H-1,2,4-triazole-3-ylthio)acetic acid salts - Gotsulya, A. S.; Гоцуля, Андрій Сергійович; Гоцуля, А. С. (Запорізький державний медичний університет, 2016)
At this stage of modern science development scientists get a lot of questions in the ﬁeld of medicine and pharmacy. The study and search of new ways for synthesis of high-performance and low-toxic substances is one of the most important questions among them. Special attention is paid to 1,2,4-triazole and xanthine. On their basis some medical drugs have been previously made and are widely used in nowadays medicine. The aim of this work was the synthesis of salts of 2-(5-((theophylline-7’-yl)methyl)-4-methyl-4H-1,2,4-triazole-3-ylthio)acetic acid and the study of their properties. Methods and results. Theophylline has been selected as starting material. Through a number of stages 7’-((3-thio-4-methyl-4H-1,2,4-triazole-5-yl)methyl)theophylline has been obtained. Salts with organic and inorganic bases have been obtained by the neutralization reaction in aqueous medium. The structure of the compounds has been conﬁrmed with elemental analysis on Elemental Vario EL cube (Elementar Analysensysteme, Germany), IR spectra (4000–400 cm-1) have been taken off the module ALPHA-T of Bruker ALPHA FT-IR spectrometer (Bruker optics, Germany). Gear Liquid Chromatography System with Mass spectrometric detector (Agilent Technologies, USA): Agilent 1260 Inﬁ nity HPLC System; single quadrupole mass spectrometer Agilent 6120 with electrospray ionization (ESI); Open LAB CDS Software. The formation of salts has been conﬁrmed by the signals corresponding to protonated amines. Conclusion. The optimal conditions of obtaining salts of 2-(5-((theophylline-7’-yl)methyl)-4-methyl-4H-1,2,4-triazole-3-ylthio)acetic acid with inorganic and organic bases have been determined. Corresponding carboxylic acid has been obtained by interaction of the resulting thiol with monochloroacetic acid in aqueous solution with double quantity of alkali and subsequent neutralization by hydrochloric acid. It has been conﬁrmed that the greatest outputs of the reaction products were observed while using water as the solvent and its further replacement of propan-1-ol or acetone. The general physical-chemical properties of the obtained compounds have been studied and a preliminary study of biological activity has been done. Сьогодні перед науковцями постає багато питань у сфері медицини та фармації, одним із найважливіших серед них є дослідження та пошук нових шляхів синтезу високоефективних і малотоксичних речовин. Особливу зацікавленість викликають похідні 1,2,4-тріазолу та ксантину. На їхній основі створено велику кількість лікарських препаратів, які широко застосовуються в сучасній медичній практиці. Мета роботи – синтез і дослідження властивостей солей 2-(5-((теофілін-7’-іл)метил)-4-метил-4Н-1,2,4-тріазол-3-ілтіо)ацетатної кислоти. Методи та результати. Як вихідну речовину обрали теофілін, на основі якого через низку послідовних стадій отримано 7’-((3-тіо-4-метил-4Н-1,2,4-тріазол-5-іл)метил)теофілін. Реакцією нейтралізації одержані солі з органічними та неорганічними основами у водному середовищі. Досліджені фізичні та хімічні властивості сполук, що отримали. Будова речовин підтверджена за допомогою елементного аналізу з використанням приладу Elementar Vario L cube (CHNS), ІЧ-спектрофотометрії (4000–400 см-1): ІЧ-спектри зняті на модулі ALPHA Т спектрометра Bruker ALPHA FT-ІR. 1H ЯМР спектри сполук записані за допомогою спектрометра «Mercury 400» (розчинник – ДМСО-d6, внутрішній стандарт – тетраметилсилан). Хромато-мас-спектральні дослідження здійснені на приладі Agilent 1100 Series LC/MSD System, спосіб іонізації – хімічна іонізація при атмосферному тиску (APCI). Утворення солей підтверджені сигналами відповідних протонованих амінів. Висновки. Встановили оптимальні умови отримання солей 2-(5-((теофілін-7’-іл)метил)-4-метил-4Н-1,2,4-тріазол-3-ілтіо)ацетатної кислоти з неорганічними та органічними основами. Взаємодією тіолу, що одержали, з кислотою монохлорацетатною у водному розчині подвійної кількості лугу з наступною нейтралізацією кислотою хлоридною отримана відповідна карбонова кислота. Підтверджено, що найбільші виходи солей як продуктів реакції спостерігали під час використання води як розчинника з наступною її заміною на пропан-1-ол або ацетон. Здійснили дослідження загальних фізичних і хімічних властивостей сполук і виконали попереднє дослідження біологічної активності. Сегодня перед учёными возникает много вопросов в сфере медицины и фармации, и одним из важнейших среди них является исследование и поиск новых путей синтеза высокоэффективных и малотоксичных веществ. Особый интерес вызывают производные 1,2,4-триазола и ксантина. На их основе создано значительное количество лекарственных препаратов, которые широко применяются в современной медицинской практике. Цель работы – синтез и исследование свойств солей 2-(5-((теофиллин-7’-ил)метил)-4-метил-4Н-1,2,4-триазол-3-илтио)ацетатной кислоты. Методы и результаты. В качестве исходного вещества выбран теофиллин, на основе которого через ряд последовательных стадий был получен 7’-((3-тио-4-метил-4Н-1,2,4-триазол-5-ил)метил)теофиллин. Реакцией нейтрализации получены соли с органическими и неорганическими основаниями в водной среде. Исследованы общие физические и химические свойства полученных соединений. Строение веществ подтверждено с помощью элементного анализа на приборе ElementarVario L cube (CHNS), ИК-спектрофотометрии (4000–400 см-1): ИК спектры были сняты на модуле ALPHA T спектрометра Bruker ALPHA FT-IR. 1H ЯМР спектры соединений записаны с помощью спектрометра «Mercury 400» (растворитель – ДМСО-d6, внутренний стандарт – тетраметилсилан). Хромато-масс-спектральные исследования проводили на приборе Agilent 1100 Series LC/MSD System, способ ионизации – химическая ионизация при атмосферном давлении (APCI). Образование солей подтверждено сигналами соответствующих протонированных аминов. Выводы. Установлены оптимальные условия получения солей 2-(5-((теофиллин-7’-ил)метил)-4-метил-4Н-1,2,4-триазол-3-илтио)ацетатной кислоты с неорганическими и органическими основаниями. Взаимодействием полученного тиола с кислотой монохлорацетатной в водном растворе удвоенного количества щёлочи с последующей нейтрализацией кислотой соляной получена соответствующая карбоновая кислота. Подтверждено, что наибольшие выходы солей как продуктов реакции наблюдались при использовании воды в качестве растворителя с последующей её заменой на пропан-1-ол или ацетон. Исследованы общие физические и химические свойства полученных соединений и предварительное исследование биологической активности.
Синтез і дослідження фізико-хімічних властивостей солей 2-(5-((теофілін-7’-іл)метил)-4-метил-4Н-1,2,4-тріазол-3-ілтіо)ацетатної кислоти
Синтез и исследование физико-химических свойств солей 2-(5-((теофиллин-7’-ил)метил)-4-метил-4Н-1,2,4-триазол-3-илтио)-ацетатной кислоты
Keywords: Theophylline; 1,2,4-triazole; Physical-Chemical Properties; Synthesis; теофілін; 1,2,4-тріазол; фізико-хімічні властивості; синтез; теофиллин; 1,2,4-триазол; физико-химические свойства